Novel SO3H-functionalized dicationic ionic liquids â A comparative study for esterification reaction by ultrasound cavitation and mechanical stirring for biodiesel production - Masri, A.N. (Elsevier B.V., 2018)
This present article covers a comparative study of esterification reaction using either ultrasound cavitation or conventional mechanical stirring with a series of newly developed SO3H-functionalized dicationic ammonium- and DABCO-based acidic ionic liquids. As a baseline for performance evaluation, esterification reaction was also conducted with a series of SO3H-functionalized monocationic ammonium-based acidic ionic liquids and several conventional mineral acids (H2SO4, etc.). Their efficacy as catalyst towards perceptive esterification for the synthesis of biodiesel from free long-chain fatty acids with methanol were appraised. The Hammett acidity of these conventional acids and acidic ionic liquids were also assessed using UVâvisible spectroscopy. Four factors were studied in the process of optimizing the reaction conditions, which are methanol to oil molar ratio (3â15), catalyst amount (0.2â1.0), temperature (25â60 Â°C) and time (0â60 min). Whereas esterification under mechanical stirring leads to formation of a triphasic system (methanol, ionic liquids and esters) easing final separation of components, the same reaction under ultrasonic irradiation leads to formation of one phase layer at the end of reaction but the esters were simply isolated using centrifugation. The results showed that whatever ultrasound or mechanical stirring, the use of dicationic ionic liquids authorized better conversion yields of free fatty acid (FFA) into fatty acid methyl esters (FAME) with better yields than with either monocationic ionic liquids or mineral acids. The novel ionic liquids together with the design of a clean procedure offers advantages including short reaction time, good yield, operational simplicity, and environmentally benign characteristics. Â© 2017 Elsevier B.V.